(untitled) (International Journal of Engineering and Computer Science, 2014)
This paper mentions a method for the automatic detection and correction of films damaged by tear. The method includes estimation of motion vectors between two frames in an image sequence, delineating the tear boundary and restoring the damaged frame using suitable missing data treatment. Thus loss of data along the tear boundary is also corrected. The paper also includes the comparison of performance of different motion estimation methods like exhaustive search, logarithmic search, diamond search and adaptive rood pattern search. Among these adaptive rood pattern search is found to be the best in performance based on the study of quality measurement and the execution time required.